2017
DOI: 10.1016/j.jacc.2017.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Treating Specialty and Outcomes in Newly Diagnosed Atrial Fibrillation

Abstract: BACKGROUND Atrial fibrillation (AF) occurs in many clinical contexts and is diagnosed and treated by clinicians across many specialties, which has been associated with treatment variation. OBJECTIVES We evaluated the association of treating specialty with AF outcomes among patients with newly-diagnosed AF. METHODS Using complete data of the TREAT-AF (The Retrospective Evaluation and Assessment of Therapies in AF) study from the Veterans Health Administration, we identified patients with newly diagnosed, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 34 publications
5
30
0
1
Order By: Relevance
“…The data in this report also demonstrate that care by outpatient cardiology providers may be linked to lower occurrence of ischemic stroke events in patients with AF. These findings are consistent with data from TREAT‐AF, which recently demonstrated that early cardiology specialty care (eg, within 90 days of diagnosis) were associated with a reduced risk of stroke, and this protective benefit possibly was related to an increased likelihood of oral anticoagulant initiation . In comparison with data from TREAT‐AF, we were able to show that, despite a higher predilection for patients to initiate oral anticoagulants when seen by a cardiology provider, the risk of bleeding does not increase.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The data in this report also demonstrate that care by outpatient cardiology providers may be linked to lower occurrence of ischemic stroke events in patients with AF. These findings are consistent with data from TREAT‐AF, which recently demonstrated that early cardiology specialty care (eg, within 90 days of diagnosis) were associated with a reduced risk of stroke, and this protective benefit possibly was related to an increased likelihood of oral anticoagulant initiation . In comparison with data from TREAT‐AF, we were able to show that, despite a higher predilection for patients to initiate oral anticoagulants when seen by a cardiology provider, the risk of bleeding does not increase.…”
Section: Discussionsupporting
confidence: 90%
“…Recent reports from specific patient populations have examined the influence of provider specialty on anticoagulation practices in patients with AF. Data from TREAT‐AF (The Retrospective Evaluation and Assessment of Therapies in AF) study demonstrated that veterans who were evaluated by a cardiology provider within 90 days of their AF diagnosis were more likely to have a dispensed prescription for warfarin than those who saw a primary care provider . Data from the ORBIT‐AF (Outcomes Registry for Better Quality Care in the Treatment of AF) also demonstrated that oral anticoagulant use (eg, warfarin or dabigatran) was higher for patients seen by cardiology providers than those treated in primary care .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even though we found that gatekeeping itself was not associated with major pharmacologic treatment differences, there may be other barriers that limit specialty referral even in non‐gated plans. We have previously reported that in newly‐diagnosed AF across the entire Veterans Affairs system, cardiology care (compared to primary care only) was associated with lower risk of stroke that was mediated by higher rates of OAC prescription . Patients who lived closer to VA specialty centers were more likely to receive cardiology care.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of AF in the United States is believed to range from 2.7 to 6.1 million, and is projected to increase to 12.1 million by 2030 . AF has widely varying treatments for stroke prevention and for rhythm management; some of these may be more accessible to patients through specialty care, such as cardiology or cardiac electrophysiology . At the same time, because of its high prevalence and wide‐ranging clinical manifestations, AF is treated by many different provider types, from primary care physicians (PCPs) to cardiovascular specialists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation